IN VITRO ANTICANCER POTENTIAL OF WHEATGRASS (TRITICUM AESTIVUM) EXTRACTS (International Journal of Environmental Sciences, 2025)
Wheatgrass have multitude effects in thalassemia, hemolytic anemia, asthma, allergy, inflammatory bowel disease and detoxification. Wheatgrass seems to be very promising herbal drug and extensive research work is needed in order to explore its therapeutic application in various diseases. An attempt was made to evaluate the anti-proliferative potentials of the Wheatgrass extracts on human breast cancer (MCF-7) cell lines, human colorectal cancer (HT-29) cell lines and human cervical cancer (HeLa) cell lines by MTT assay. Ethanol extract of wheatgrass were found more effective in in vitro anticancer activity in MTTT assay.